International Conference on Application and Design in Mechanical Engineering (ICADME) 2012 'Innovation and evolution in mechanical application' - Anon (Universiti Malaysia Perlis, 2012)
International Conference on Application and Design in Mechanical Engineering (ICADME) 2012 organized by School of Mechatronic Engineering, 27th - 28th February 2012 at Bayview Beach Resort, Penang, Malaysia.